The Influence of Healthy Lifestyle on Purchase Intention of Healthy Beverage MSME Products, Fruve Juicery, Mediated by Perceived Value - Frisca Karlina Soinbala; Baiq Handayani Rinuastuti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
As public awareness of healthy consumption patterns in Indonesia increases, consumer preferences for health-based products are increasing, which in turn influencesPurchase intention through evaluation of product perceived value, based on this phenomenon, this study aims to analyze the influence of Healthy Lifestyle on Purchase Intention of Fruve Juicery healthy drink products with Perceived Value as a mediating variable. This study uses a quantitative approach with a causal associative design through a survey method. Data were collected from 100 respondents who were selected purposively in Mataram City, aged at least 16 years and have knowledge about Fruve Juicery products. The research instrument used a questionnaire measured with a Likert scale. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 4.0 software to test the validity, reliability, and research hypotheses. The results showed that a healthy lifestyle has a positive and significant effect on purchase intention, both directly and through perceived value as a mediating variable. In addition, perceived value has been shown to play an important role in increasing consumer purchase intention for MSME healthy drink products. These findings indicate that consumer perceived value is a key mechanism in linking a healthy lifestyle to purchasing decisions. Therefore, healthy beverage MSMEs need to improve consumer value perception by improving product quality and optimizing digital marketing strategies to strengthen consumer purchasing intentions.